Oral subcutaneous midline leiomyomatous hamartoma presenting as congenital incisive papilla overgrowth in a toddler - Ashish Loomba; Shalini Garg; Abhishek Dhindsa; Harshaminder Kaur; Neetu Jain; Promila Dhindsa (Wolters Kluwer Medknow Publications, 2017)
Congenital soft-tissue tumors of oral cavity are mostly hyperplastic and benign in nature. This article presents an unusual case of congenital subcutaneous hamartoma of incisive papilla in a 2-year-old female child causing feeding and breathing difficulty. Total excisional biopsy was done under local anesthesia. Histopathology of tissue in reticulin-stained slide showed the presence of immature muscle fibers whereas Masson's trichrome stain revealed collagen fibers and smooth muscles confirming the diagnosis of oral midline subcutaneous smooth muscle (leiomyomatous) hamartoma of incisive papilla. It is important for dental professionals to be aware of this oral lesion present from birth mimicking overgrowth of incisive papilla, by its presentation, differential diagnosis, histopathology, and management.